Analisis Kesulitan Belajar Siswa Kelas XI TKJ SMK Teknologi dalam Pelajaran Matematika Materi Limit: Penelitian - Yayan Diansyah; Agus Purwanto; Irma Charlin Oktaviani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify any factors that cause students in class XI TKJ Technologi to have difficulty in studying mathematics in the Limit material. Types and approaches in this research are descriptive research types with qualitative approaches. In this study three techniques were collected, namely by tests, observations and questionnaires. As for analyzing data from test results, observations, and questionnaires using the percentage formula. The findings obtained information that the difficulty of students still find it difficult to learn the material Limit. Difficulties experienced by students are students still lacking in understanding the concept of limit material, students are still lacking in understanding the prerequisite material for mathematical limit material such as algebra and trigonometry, students memorize more steps in working on problems so students will find it difficult when the form of questions changes, students still lazy to repeat the material that has been explained, students still feel afraid of the subject teacher so that when the learning process takes place, students are still reluctant to ask questions. also the teacher's habits in learning mathematics only by taking notes on the blackboard, then students lack the desire to complete the example problems given by the teacher. The hypothesis is correct that there are learning difficulties in the process of learning mathematics on the Limit material for class XI TKJ students at SMK Teknologi.